ANALISIS SISTEM PELAYANAN DI STASIUN TAWANG SEMARANG DENGAN METODE ANTRIAN - Nursihan Nursihan; Sugito Sugito; Hasbi Yasin (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Semarang Tawang Station is one of the stations visited by customers. As it is known that the train journey into one of the fastest alternative but to use other means of transportation. Therefore, it is necessary to analyze queuing model that describes the conditions to determine the size of the performance of the system to see how the service provided. When the distribution is a Poisson arrival or services or the exponential model (M) but if the distribution is not Poisson or exponential, the model General (G). Model queue at the station with the number of arrivals and the number of services is (M/M/5):(GD/∞/∞). Keywords: Processqueue, Semarang Tawang station, queuing models.